LEARNING ACHIEVEMENT OF ELEMENTARY SCHOOL STUDENTS IN URBAN SLUMS OF VARANASI CITY: A COMPARATIVE STUDY - Singh, Jai (THE PRIMARY TEACHER, 2011)
Our country is a sovereign socialist secular democratic republic committed to provide quality elementary education to all children including deprived children in the age group of 6 to 14 in the society. The slum children come from most deprived and downtrodden sections of the population in urban areas. As such, the country has a special responsibility for their education and welfare. In order to provide quality elementary education to slum children, learning achievement of students should be satisfactory. In this research paper, the learning achievement of elementary school students in Varanasi slum areas has been assessed and compared with learning achievement of elementary school students at national level. Descriptive survey method was used in the study. The study was conducted in randomly selected sample of 67 (32 government and 35 private) elementary schools in urban slum areas of Varanasi city. The subjects of the study were 670 students of Class V of these sampled elementary schools. Data was analyzed using per centage method, bar-diagram and t-test. Learning achievement of students of elementary schools in slum areas of Varanasi city was not found satisfactory and the learning achievement of the students of government elementary schools in slum areas was found significantly less than that of the students of private elementary schools. Furthermore, learning achievement of students in slum areas was found significantly less than learning achievement of elementary school students at national level.